Character-Based Perceptions of Plagiarism in Scientific Writing: A Study of Islamic Religious Education Lecturers - Endis Firdaus; Aceng Kosasih; Makhmud Syafe'i; Alwan Husni Ramdani; Muhammad Nurfaizi Arya Rahardja (The Faculty of Tarbiyah and Teacher Training associated with PSPII, 2025)
Plagiarism remains a significant challenge in academic writing, especially in higher education contexts where scholarly integrity is paramount. This study aims to analyze the experiences of Islamic Religious Education (IRE) lecturers as researchers and authors in developing anti-plagiarism awareness and ethical writing practices. Drawing upon key factors related to plagiarism identified in prior literature, this study explores participants’ character-based awareness and perceptions of plagiarism. A qualitative research design was employed, involving purposive sampling and data collection through artifact analysis and semi-structured interviews. The findings reveal that participants demonstrate varying levels of understanding and internalization of anti-plagiarism values shaped by personal character, institutional support, and academic norms. These insights offer practical recommendations for fostering academic integrity and emphasize the role of character education in developing ethically responsible scholars. The study contributes to the discourse on plagiarism prevention by highlighting the intersection between character formation and scholarly writing in religious education settings.